Inherited Disorders of Thyroid Hormone Metabolism Defect Caused by the Dysregulation of Selenoprotein Expression - Lee, Kyu Won; Shin, Yoochan; Lee, Sungahn; Lee, Sihoon (Frontiers in Endocrinology, 2022)
Consistent activation and functioning of thyroid hormones are essential to the human body as a whole, especially in controlling the metabolic rate of all organs and systems. Impaired sensitivity to thyroid hormones describes any process that interferes with the effectiveness of thyroid hormones. The genetic origin of inherited thyroid hormone defects and the investigation of genetic defects upon the processing of thyroid hormones are of utmost importance. Impaired sensitivity to thyroid hormone can be categorized into three conditions: thyroid hormone cell membrane transport defect (THCMTD), thyroid hormone metabolism defect (THMD), and thyroid hormone action defect (THAD). THMD is caused by defects in the synthesis and processing of deiodinases that convert the prohormone thyroxine (T4) to the active hormone triiodothyronine (T3). Deiodinase, a selenoprotein, requires unique translation machinery that is collectively composed of the selenocysteine (Sec) insertion sequence (SECIS) elements, Sec-insertion sequence-binding protein 2 (SECISBP2), Sec-specific eukaryotic elongation factor (EEFSEC), and Sec-specific tRNA (TRU-TCA1-1), which leads to the recognition of the UGA codon as a Sec codon for translation into the growing polypeptide. In addition, THMD could be expanded to the defects of enzymes that are involved in thyroid hormone conjugation, such as glucuronidation and sulphation. Paucity of inherited disorders in this category leaves them beyond the scope of this review. This review attempts to specifically explore the genomic causes and effects that result in a significant deficiency of T3 hormones due to inadequate function of deiodinases. Moreover, along with SECISBP2, TRU-TCA1-1, and deiodinase type-1 (DIO1) mutations, this review describes the variants in DIO2 single nucleotide polymorphism (SNP) and thyroid stimulating hormone receptor (TSHR) that result in the reduced activity of DIO2 and subsequent abnormal conversion of T3 from T4. Finally, this review provides additional insight into the general functionality of selenium supplementation and T3/T4 combination treatment in patients with hypothyroidism, suggesting the steps that need to be taken in the future.